Development of Google Sites Based Collaborative Learning Media Assisted by Google Docs for Correspondence Learning among Eleventh Grade Office Management Students at SMK Negeri 16 Jakarta - Sabrina Aisya Putri; Dewi Nurmalasari; Susan Febriantina (The Future of Education Journal, 2026)
This study aims to develop a collaborative learning media based on Google Sites assisted by Google Docs for the correspondence element in Grade XI Office Management students and to determine the feasibility and practicality of the developed media. The study employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through validation questionnaires involving one material expert and one media expert, as well as student response questionnaires involving 36 Grade XI Office Management students. The results showed that the developed collaborative learning media achieved a feasibility score of 93.5% categorized as “Very Feasible” and a practicality score of 95% categorized as “Very Practical”. These findings indicate that the developed media meets the needs of correspondence learning and supports students’ collaborative activities in official letter-writing practices. Therefore, the Google Sites-based collaborative learning media assisted by Google Docs is considered feasible and practical to support correspondence learning and facilitate collaborative letter-writing activities.